Species of Moguai Tan and Ng, 1999 (Decapoda: Brachyura: Camptandriidae) from brackish waters in the Ryukyu Islands, Japan, with the description of a new species - Naruse, Tohru (Zootaxa, 2005)
Two species of Moguai Tan & Ng, 1999 (Camptandriidae) are recorded from the Ryukyu Islands, Japan, one of which is new to science. Moguai pyriforme, sp. nov. is distinguished from other two congeners by its narrower front and the anterolateral margin being located inside the branchial region. Moguai elongatum is recorded from Japan for the first time, and its geographical distribution extended east from Fukien Province, China. A key to the species of Moguai is provided.